Multidrug resistance in the neonatal unit and its therapeutic implications - Rinawati Rohsiswatmo (Paediatrica Indonesiana, 2006)
Background Neonatal septicemia constitutes an important causeof morbidity and mortality among neonates in Indonesia. The ex-cessive use of antibiotics may cause antibiotic resistant bacteriaand may cause neonatal fungal infection.Objective To investigate the spectrum of organisms which causeneonatal sepsis and assess their sensitivity to various groups ofdrugs in the neonatal unit.Methods A prospective study conducted on newborn babies de-livered in Cipto Mangunkusumo Hospital, Jakarta from July 2004-May 2005 who presented clinical signs of septicemia were sub-jected for blood culture. Those sensitive to antibiotics for 7 daysyet showed no clinical improvement were also cultured for fungi.Results A total of 499 blood cultures were taken, 320 were posi-tive for bacteria (positivity rate was 65.3%). There were 192 samplescultured for fungi, and the positivity rate was 64% (all for Candidasp). Acinetobacter calcoaceticus was the most common bacteriafound (35.7%), followed by Enterobacter sp (7.0%), and Staphylo-coccus sp (6.8%). Most bacteria showed high degrees of resis-tance to commonly used antibiotics (ampicillin and gentamicin).There were also high degrees of resistance to cephalosporins byboth Gram negative and Gram positive organisms. Only 61.7% ofA. calcoaceticus, and 45.7% of Enterobacter sp were sensitive toceftazidime. Gram negative organisms were also highly resistantto amikacin, but Staphylococcus sp was only moderately resis-tant. Resistance to carbapenem (meropenem and imipenem) var-ied from moderate to low. Drugs which were not used for newbornbabies (quinolones/ciprofloxacin and chloramphenicol) varied frommoderate to high resistance.Conclusion Neonatal sepsis remains one of the major causes ofmortality in our neonatal unit. Most organisms have developedmultidrug resistance, and management of patients infected withthese organisms and especially those with fungi infection are be-coming a problem in developing countries